Dementia stigma: representation and language use - Putland, Emma; Brookes, Gavin (Journal of Language and Aging Research, 2024)
Linguistic choices are widely understood to have the potential to contribute to, but also to challenge, dementia stigma. This scoping review therefore aims to better understand: 1) the characteristics of language-oriented studies into representations of dementia and people with dementia, particularly regarding theoretical engagement with dementia stigma; and 2) what specific linguistic features have the potential to contribute to and/or challenge dementia stigma. Using Scopus, PubMed, PsychInfo and Google Scholar, 44 papers published between January 2000 and December 2022 were selected and thematically synthesized. We found that the number of publications addressing language and dementia stigma increased dramatically over the period covered. Most studies (75 %) did not explicitly define their use of the term stigma, and those that did drew on a range of theories and sources. Linguistic features associated with stigma included catastrophizing metaphors and the personification of dementia as a cruel enemy. Distancing and delegitimizing strategies were popularly used for people living with dementia, including homogenization, negative group labels, dehumanizing metaphors, infantilization and passivization. Humor could be used to perpetuate dementia stigma, but also to resist and reclaim stigmatizing discourses. Dementia stigma could be challenged through redefining the roles attributed to social actors, directly critiquing harmful discourses, and by providing counter-discourses. Counter-discourses used normalizing, holistic, person-centerd, rights-based, optimistic and affirmative language. Overall, a complex picture of language and dementia stigma emerges. Based on our review of the 44 papers considered, we argue that much language has the potential to perpetuate or resist stigma, and that this is shaped by and depends upon the broader discursive context within which such language use takes place.